Exploring gendered experiences of time-use agency in Benin, Malawi, and Nigeria as a new concept to measure women’s empowerment - Eissler, Sarah; Heckert, Jessica; Myers, Emily; Seymour, Greg; Sinharoy, Sheela; Yount, Kathryn M. (International Food Policy Research Institute, 2021)
Time use, or how women and men allocate their time, is an important aspect of empowerment. To build on this area of study, we propose and explore the concept of time-use agency in this paper, which shifts the focus from the amount of time spent on activities to the strategic choices that are made regarding how to allocate time. We draw on 92 interviews from qualitative studies in Benin, Malawi, and Nigeria to explore across contexts the salience of time-use agency as a component of women’s empowerment. Our results indicate that time-use agency is salient among both women and men and dictates how women and men are able to make and act upon strategic decisions related how they allocate their time. Our findings suggest that time-use agency is important for fully understanding empowerment with respect to time use. Importantly, this study highlights the gendered dynamics and barriers women face in exercising their time-use agency. These barriers are tied to and conditioned by social norms dictating how women should spend their time. Women often make tradeoffs throughout any given day with respect to their time, balancing their expected priorities with the barriers or limitations they face in being able to spend any additional time on tasks or activities that further their own strategic goals. Additionally, these results on time-use agency echo similar themes in the literature on gendered divisions of labor, time poverty, and decision-making, but also add new subtleties to this work. For example, we find that women can easily adjust their schedules but must carefully navigate relationships with husbands to be able to attend trainings or take on new income generating activities, results that align with previous findings that women consistently have higher involvement in small decisions compared to large ones. While these themes have been observed previously in studies of women’s empowerment, to our knowledge, our study is the first to connect them to time use and time-use agency. Our study contributes the conceptualization of time-use agency, and the identification of themes relevant to time-use agency, through the emic perspectives of women and men across three diverse settings in Sub-Saharan Africa. As a concept, time-use agency goes beyond measuring time use to understand the gendered dynamics around controlling one’s time use to advance their own strategic goals and highlights any barriers one faces in doing so. It is a particularly relevant concept for interventions that aim to increase (or at least, not diminish) women’s empowerment by promoting women’s involvement in remunerated activities. Although time-use agency, as a concept, has yet to be addressed in women’s empowerment literature. A next step in this area of inquiry is to develop survey indicators on time-use agency, which may reduce bias and cognitively burden compared to existing time use surveys.